Prevalence of Psoriasis in Cases Diagnosed with Fissured And/or Geographic Tongue in Clinics of College of Dentistry- Hawler Medical University: A Retrospective- Prospective- Study - Sameeh Sdiq Omer; Rezao Omar Hasan; Sarkwat Hamad Ali; Hassan Ali Mahmood Al Barzanjy (Erbil Dental Journal, 2025)
Background: Both psoriasis and tongue surface changes like fissured and geographic tongue are sharing some common features like surface changes nature, inflammation process and linking to autoimmune. There is a chance for these conditions to occur simultaneously.